Antibiotic Treatment Induces Long-lasting Changes in the Fecal Microbiota that Protect Against Colitis. Issue 10 (October 2016) - Ward, Naomi L.; Phillips, Caleb D.; Nguyen, Deanna D.; Shanmugam, Nanda Kumar N.; Song, Yan; Hodin, Richard; Shi, Hai Ning; Cherayil, Bobby J.; Goldstein, Allan M.
Abstract : Background: The interplay between host genetics, immunity, and microbiota is central to the pathogenesis of inflammatory bowel disease. Previous population-based studies suggested a link between antibiotic use and increased inflammatory bowel disease risk, but the mechanisms are unknown. The purpose of this study was to determine the long-term effects of antibiotic administration on microbiota composition, innate immunity, and susceptibility to colitis, as well as the mechanism by which antibiotics alter host colitogenicity. Methods: Wild-type mice were given broad-spectrum antibiotics or no antibiotics for 2 weeks, and subsequent immunophenotyping and 16S rRNA gene sequencing–based analysis of the fecal microbiome were performed 6 weeks later. In a separate experiment, control and antibiotic-treated mice were given 7 days of dextran sulfate sodium, 6 weeks after completing antibiotic treatment, and the severity of colitis scored histologically. Fecal transfer was performed from control or antibiotic-treated mice to recipient mice whose endogenous microbiota had been cleared with antibiotics, and the susceptibility of the recipients to dextran sulfate sodium–induced colitis was analyzed. Naive CD4 + T cells were transferred from control and antibiotic-treated mice to immunodeficient Rag-1 −/− recipients and the severity of colitis compared. Results: Antibiotics led to sustained dysbiosis and changes in T-cell subpopulations, including reductions in colonic lamina propria total T cells and CD4 + T cells. Antibiotics conferred protection against dextran sulfate sodium colitis, and this effect was transferable by fecal transplant but not by naive T cells. Conclusions: Antibiotic exposure protects against colitis, and this effect is transferable with fecal microbiota from antibiotic-treated mice, supporting a protective effect of the microbial community. Abstract : Supplemental Digital Content Is Available in the Text.Article first published online 8 September 2016.